Pengaruh Harga, Promosi, dan Kemudahan Penggunaan Aplikasi Terhadap Keputusan Pembelian Pada Marketplace Shopee (Studi Kasus Mahasiswa Universitas Islam Malang Fakultas Ekonomi dan Bisnis Angkatan 2019) - Ahmad Fahmil Fithriyansyah; N. Rachma; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract In the digital era, technology is now increasingly advanced and developing. We can use cell phones for everything we need simply, quickly and instantly. For example, such as payment transactions, online motorbike taxi rides, culinary orders, address search, we can even shop for daily necessities through online applications. The purpose of this study was to find out and analyze the effect of price, promotion and ease of use in purchasing decisions for the Shopee marketplace. The population in this study were active students of the Faculty of Economics and Business, Islamic University of Malang, class of 2019 who had purchased at Shopee. The approach method uses a non-probability sampling technique, namely purposive sampling which is a sampling technique based on certain criteria using a questionnaire distributed to 100 respondents and using the SPSS analysis tool. The results of the study show that partially the price, promotion, and ease of use of the application have a positive and significant effect on purchasing decisions. Simultaneously price, promotion, and ease of use of the application have a positive and significant effect on purchasing decisions. Keywords: Price, Promotion, Ease of Use of the Application, Purchase Decision